2012
DOI: 10.1155/2012/601242
|View full text |Cite
|
Sign up to set email alerts
|

Leishmaniasis and Climate Change—Case Study: Argentina

Abstract: Vector-borne diseases closely associated with the environment, such as leishmaniases, have been a usual argument about the deleterious impact of climate change on public health. From the biological point of view interaction of different variables has different and even conflicting effects on the survival of vectors and the probability transmission of pathogens. The results on ecoepidemiology of leishmaniasis in Argentina related to climate variables at different scales of space and time are presented. These st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0
12

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 83 publications
2
41
0
12
Order By: Relevance
“…Temperature and humidity have positive effects on the activity and abundance of phlebotomine sand flies, which depends on the species [47,58]. In the neighbouring state of Rio de Janeiro, L .…”
Section: Discussionmentioning
confidence: 99%
“…Temperature and humidity have positive effects on the activity and abundance of phlebotomine sand flies, which depends on the species [47,58]. In the neighbouring state of Rio de Janeiro, L .…”
Section: Discussionmentioning
confidence: 99%
“…Also, Argentina recorded outbreaks in the Bella Vista, Formosa, and Salta Counties [31, 32]. In addition, the El Niño-Southern Oscillation (ENSO) has caused a growth of deforestation and of the Phlebotomine population, which has led to the rise of occurrence of CL [3336]. Studies conducted in Colombia showed an association between increase of CL incidence rates during the El Niño and decline during the La Niña [4, 23].…”
Section: Discussionmentioning
confidence: 99%
“…In Colombia, the probability of CL presence based on ecological zones and environmental variables was explored by King et al (2004) [27]. In Argentina, Salomón et al (2012) [28] modeled CL incidence using maximum entropy modeling. To date, efforts for estimating the associated risk and the predicted spatial distribution of leishmaniasis in Brazil are limited to small geographical areas.…”
Section: Introductionmentioning
confidence: 99%